Persistent Antihypertensive Effect of Oral Nitrite Supplied up to One Year via the Drinking Water in Spontaneously Hypertensive Rats - Haas, Maria; Georg Classen, Hans; Thöni, Hanspeter; Georg Classen, Ulf; Drescher, Birgit (Arzneimittelforschung, 1999)
The hypothesis was studied whether the chronic administration of nitrite lowers the blood pressure of spontaneously hypertensive rats (SHR) and prevents secondary hypertension-induced organ lesions. For this purpose totally 96 SHR received 50 to 75 mmol/l NaNO2 or equimolar amounts of NaHCO3 in their drinking water during 4, 8 or 12 months. At each point of time arterial blood pressure, determined with the tail cuff method, was significantly lower in the NaNO2-group in comparison to the controls indicating that no significant tolerance towards nitrite had developed. There was also a tendency towards reduced cardiac hypertrophy and renal atrophy in the NaNO2-group, however without reaching the level of significance. Drinking water containing 75 mmol NaNO2/l was not well tolerated by young rats in contrast to 50 mmol/l. Possible beneficial effects of high dietary nitrate/nitrite levels are discussed with respect to the low frequency of hypertension observed in vegetarians.
Keywords: Blood pressure; Nitrate; Nitric oxide; Nitrite, antihypertensive effect, rat